2013
DOI: 10.1111/jnc.12203
|View full text |Cite
|
Sign up to set email alerts
|

AZD1080, a novel GSK3 inhibitor, rescues synaptic plasticity deficits in rodent brain and exhibits peripheral target engagement in humans

Abstract: Abnormal tau phosphorylation resulting in detachment of tau from microtubules and aggregation are critical events in neuronal dysfunction, degeneration, and neurofibrillary pathology seen in Alzheimer's disease. Glycogen synthase kinase3b (GSK3b) is a key target for drug discovery in the treatment of Alzheimer's disease and related tauopathies because of its potential to abnormally phosphorylate proteins and contribute to synaptic degeneration. We report the discovery of AZD1080, a potent and selective GSK3 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 34 publications
(40 reference statements)
3
85
0
Order By: Relevance
“…Moreover, potent GSK-3 inhibition can lead to toxicity (as occurs with lithium treatment in the brain, causing motor deficits 104 ), so care must be taken to only mildly inhibit the enzyme. AZD1080, a GSK-3 inhibitor from AstraZeneca, exhibited some success in limited phase I clinical trials for Alzheimer’s disease, but blood glucose was not measured 105 . Another GSK-3 inhibitor, tideglusib (Noscria), was used in a phase II clinical trial for progressive supranuclear palsy 106 .…”
Section: Strategies To Modulate Liver Glucose and Glycogen Metabolismmentioning
confidence: 99%
“…Moreover, potent GSK-3 inhibition can lead to toxicity (as occurs with lithium treatment in the brain, causing motor deficits 104 ), so care must be taken to only mildly inhibit the enzyme. AZD1080, a GSK-3 inhibitor from AstraZeneca, exhibited some success in limited phase I clinical trials for Alzheimer’s disease, but blood glucose was not measured 105 . Another GSK-3 inhibitor, tideglusib (Noscria), was used in a phase II clinical trial for progressive supranuclear palsy 106 .…”
Section: Strategies To Modulate Liver Glucose and Glycogen Metabolismmentioning
confidence: 99%
“…In consistent with this homology, many GSK-3b inhibitors are also potent inhibitors of CDKs [22][23][24][25]. Selectivity is thus considered as a major issue to develop potent GSK-3b inhibitors as probes for biological functions of GSK-3b and drugs for the treatment of various diseases [18,[26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, several compounds have been developed to inhibit GSK-3 activity, such as tideglusib and AZD1080. However, the former completed a phase II study without demonstrating significant clinical improvements in subjects with AD, whereas AZD1080 has completed a phase I trial with a confirmed target engagement and good safety and tolerability profiles [23].…”
mentioning
confidence: 99%